The Limited English Proficiency Patient Family Advocate Role: Fostering Respectful and Effective Care Across Language and Culture in a Pediatric Oncology Setting. (May 2016) - Gil, Stephanie; Hooke, Mary C.; Niess, Dawn
Patients and families with limited English proficiency (LEP) face a multitude of barriers both inside and outside the hospital walls. These barriers can contribute to difficulty accessing care and understanding/adhering to treatment recommendations, ultimately placing them at higher risk for poorer outcomes than their English-speaking counterparts. The LEP Patient Family Advocate role was created with the aim of improving access, promoting effective communication, and equalizing care for children with cancer from families with LEP. The goal of this mixed methods study was to describe the level of satisfaction and experiences of parents and health care providers who used the LEP Patient Family Advocate while receiving or providing care. Twelve parents and 15 health care providers completed quantitative surveys and an open-ended question about their experiences. High levels of satisfaction were reported. Themes about the role from qualitative responses included its positive effect on communication, trust, and connectedness between parents and staff. Continuity of care and safety were improved, and parents thought the role helped decrease their stress. The LEP Patient Family Advocate has a positive influence on family-centered cultural care.